THE INFLUENCE OF SOCIAL MEDIA MARKETING CAPABILITY AND DIGITAL CUSTOMER ENGAGEMENT ON MARKETING PERFORMANCE THROUGH TRUST - Dede Suleman; Velly Anatasia; Devy Sofyanty; Prisca Nurmala Sari (ZILLZELL MEDIA PRIMA, 2026)
This study examines the influence of Social Media Marketing Capability and Digital Customer Engagement on Marketing Performance, with Customer Trust as a mediating variable among Micro, Small, and Medium Enterprises in Indonesia. A quantitative explanatory approach was employed using survey data collected from 200 respondents through an online questionnaire. The data were analyzed using Structural Equation Modeling based on Partial Least Squares. The findings reveal that Social Media Marketing Capability and Digital Customer Engagement have positive and significant effects on Marketing Performance. Both variables also significantly influence Customer Trust, indicating their role in building strong customer relationships in digital environments. Furthermore, Customer Trust is found to have a significant effect on Marketing Performance and acts as a mediating variable in the relationships between Social Media Marketing Capability and Marketing Performance, as well as between Digital Customer Engagement and Marketing Performance. These results highlight the importance of integrating digital capabilities, customer engagement, and trust-building strategies to achieve optimal marketing outcomes. This study contributes to the development of relationship marketing literature by providing empirical evidence from the context of Indonesian MSMEs. The findings also offer practical implications for business practitioners in enhancing digital marketing effectiveness.